Mejores Prácticas de Manejo en el Area Agrícola de los Everglades: Controlando el Fósforo en Partícula y Sedimentos en Canales - Orlando A. Diaz; Timothy A. Lang; Samira H. Daroub; Viviana M. Nadal (EDIS, 2007)
SL-228-Sp, a 9-page illustrated fact sheet by O.A. Diaz, T.A. Lang, S.H. Daroub, and V.M. Nadal, is the Spanish language version of "SL228/SS448: Best Management Practices in the Everglades Agricultural Area: Controlling Particulate Phosphorus and Canal Sediments." It explains and discusses particulate P and sediment control practices, which serve as important tools in efforts to improve water quality in the basin. This EDIS article is one in a series that attempts to explain in easily understandable terms the implementation methods and rationale behind the main P load reducing BMPs employed on EAA farms. Published by the UF Department of Soil and Water Sciences, August 2007.